Cost Benefit Analysis of Village Fund Management for Improving Education in Sukomulyo Village, Jombang Regency - Mustofa, Amirul; Anggara, Febrian Ari (ADMAN: Journal of Contemporary Administration and Management, 2023)
This research aims to analyze the use of village funds to improve children's education and reading parks in Sukomulyo Village, Jombang Regency. The collection technique involves collecting existing documents in the village and interviews. After the data is collected, interactive analysis is carried out to test the validity of the data and discuss the data with the theory used. The research results show that the village fund program in Sukomulyo Village has been used to build facilities and infrastructure for Early Childhood Education, Kindergarten, and Reading Park buildings. Second, developing children's education facilities and infrastructure has involved all village officials, the community, religious leaders, and other stakeholders from planning to accountability. Third, the cost and benefit analysis results show that all stakeholders agree that the benefits of the children's education development program are higher than the losses. The implication is that the Sukomulyo village government is obliged to prioritize education programs funded by village funds every year so that children's education interests become a priority program.